PELEMBAGAAN PARTAI KEBANGKITAN BANGSA (PKB) DALAM PEMILU LEGISLATIF TAHUN 2024 DI KABUPATEN NAGEKEO - Deprian L. R. Oy Nuwa; Rodriques Servatius; Urbanus Ola (Journal Education and Government Wiyata, 2025)
This research is entitled Institutionalization of the National Awakening Party (PKB) in the 2024 Legislative Election in Nagekeo Regency. The main aim of this research is to describe and analyze the institutionalization of the National Awakening Party (PKB) in the 2024 Legislative Election in Nagekeo Regency. The research method used is descriptive qualitative with interview, observation and documentation techniques. The research results show that the procedures and mechanisms for recruiting legislative candidates (legislative candidates) for the National Awakening Party (PKB) in Nagekeo Regency based on PKB Regulation Number 7 of 2017 concerning Technical Instructions for Recruitment and Selection of Candidates for National Awakening Party Legislative Members for the General Election are designed professionally, transparently and strategic to increase the number of seats and votes obtained by PKB Nagekeo Regency in the 2024 Election and strengthen PKB institutions in Nagekeo Regency. DPC PKB Nagekeo Regency succeeded in demonstrating strategic adaptation to the social and demographic characteristics of Nagekeo Regency, where the majority of the population is Catholic, through inclusive cadre formation and accommodating local identity.